Extended amygdala connectivity changes during sustained shock anticipation. Issue 1 (December 2018) - Torrisi, Salvatore; Gorka, Adam; Gonzalez-Castillo, Javier; O'Connell, Katherine; Balderston, Nicholas; Grillon, Christian; Ernst, Monique
Abstract The bed nucleus of the stria terminalis (BNST) and central amygdala (CeA) of the extended amygdala are small, anatomically interconnected brain regions. They are thought to mediate responses to sustained, unpredictable threat stimuli and phasic, predictable threat stimuli, respectively. They perform these operations largely through their interconnected networks. In two previous studies, we mapped and contrasted the resting functional connectivity networks of the BNST and CeA at 7 Tesla with high resolution. This follow-up study investigates the changes in functional connectivity of these structures during sustained anticipation of electric shock. Results show that the BNST and CeA become less strongly coupled with the ventromedial prefrontal cortex (vmPFC), cingulate, and nucleus accumbens in shock threat relative to a safety condition. In addition, the CeA becomes more strongly coupled with the thalamus under threat. An exploratory, whole-brain connectivity analysis reveals that, although the BNST/CeA exhibits generally decreased connectivity, many other cortical regions demonstrate greater coupling under threat than safety. Understanding the differential network structures of these two regions and how they contribute to processing under threat will help elucidate the building blocks of the anxious state.